BLOOD VISCOSITY AS A DETERMINING FACTOR OF ISCHEMIC STROKE OUTCOMES EVALUATED WITH NIHSS AND MRS ON DAY 7 AND 30 POST-THROMBOLYSIS - Rasyid, Al; Harris, Salim; Kurniawan, Mohammad; Mesiano, Taufik; Hidayat, Rakhmad; Meisadona, Gogor (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: This study aimed to analyze blood viscosity as a determining factor of ischemic stroke outcomes evaluated with National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) on day 7 and 30 post-thrombolysis. Methods: This study was a 4-months cohort study taking place in Cipto Mangunkusumo General Hospital from January to April 2017. Subjects were collected at the Emergency Department or Neurology Outpatient Department. Eligible patients gave informed consent. Patients underwent numerous examinations, including blood viscosity test using digital microcapillary (DM) instrument. Outcomes of patients were identified on day 7 and day 30 post-thrombolysis using NIHSS and mRS, respectively. Results: Most acute ischemic stroke patients (88.6%) had blood hyperviscosity. 9.1% patients had poorer neurologic deficit on day 7 evaluated with NIHSS and 18.2% patients had poor outcome on day 30 evaluated with mRS. All patients with normal blood viscosity did not have a poorer neurologic deficit on day-7-evaluation. Conclusion: Blood viscosity determines the outcomes of acute ischemic stroke patients on day 7 and day 30 post-thrombolysis.